Escrita acadêmica e avaliação: o uso de reforços e atenuadores em artigos científicos publicados em inglês por pesquisadores brasileiros - Monica Soares de Araujo Guimaraes (2009)
Studies on modality items as hedges and boosters show its relevance to the academic writing. This study investigates the use by researchers affiliated to national research centers, the presence of boosters and hedges in their academic research papers, published in English, and compares it to texts published by researchers affiliated to international research centers that publish their papers in English, as well. Based onSwales (1993, 1996, 2000), Hyland (1996a, 1996b, 2000, 2004), Salager-Meyer (1994), we analyzed two subcorpora consisting of thirty articles published by each research group. The lexicogrammatical features of boosters and hedges were selected from a list compiled by Hyland (2000), which had been identified in the sections that make up the rhetorical articles and categorized into lexical verbs, modal verbs, adverbs, adjectives and nouns. Boosters and hedges were further classified according to Salager-Meyer (1994) as shields and/or as approximators. Our investigation indicates that the researchers in both subcorpora use boosters and hedges in their writings; however,researchers affiliated to international research centers tend to use these features more frequently than researchers affiliated to national research centers. The analysis of the surface structure, as we computed the data in the two subcorpora together, shows that we had the same lexicogrammatical classes used in both. We notice that when theclasses were analyzed as hedges, the researchers of both subcorpora use the same lexicogrammatical classes. However, the classes used by researchers in both subcorpora were different when boosters were analyzed. Boosters and the hedges were used as shields and/or approximators (see Salager-Meyer, 1994) in both subcorpora. Weconclude that the choices of using boosters and hedges are related to the communicative purpose of each of the rhetorical sections of the articles. Researchers affiliated to national research centers tend to use these features in different ways especially regarding to research article sections, as the researched literature indicates the sections of Materials and Methods show low use of hedges and both subcorpora presentdivergent data.